The masking property of the auditory system: The masking of speech signals - Johan J. Hanekom (South African Journal of Communication Disorders, 1995)
The masking property of the auditory system is well known in the context of two-tone masking. For complex (speech) signals, the effects of masking are less well known. This paper explores the masking of speech signals, by calculating which parts of the speech signal is inaudible because of masking. The theory for the masking of one tone by another is expanded, to establish an equation for the masking threshold. This masking threshold takes into account the masking of each frequency component on all other frequency components. Speech is then synthesized in which the supposedly inaudible parts of the speech signal are discarded, and the effects are evaluated in a very simple psychoacoustic experiment. It is shown that the information below the masking threshold is indeed redundant.